Education Leadership Programs Responding to Current American Crises - James Coaxum; Michael Farrow; JoAnn Manning (Impacting Education, 2022)
The 2020 global pandemic has further exacerbated the inequities suffered by our most vulnerable students.  Here in the United States, the intersection of two pandemics have raised major issues surrounding racial discrimination, civil rights, and equal justice. This essay details one university responding to the current American crises in three areas that are pertinent to leadership preparation programs: recruitment, curriculum, and the problem in practice dissertation. By sharing our experiences and the literature that guides our actions, this paper aims to inspire education leadership programs to revitalize their efforts to support education leaders committed to social justice.